Data Equivalency of an Interactive Voice Response System for Home Assessment of Back Pain and Function - William S Shaw; Santosh K Verma (Pain Research and Management)
BACKGROUND: Interactive voice response (IVR) systems that collect survey data using automated, push-button telephone responses may be useful to monitor patients’ pain and function at home; however, its equivalency to other data collection methods has not been studied.